Embedding Anti-Corruption Values in Citizenship Courses at Budi Darma University Medan - Sumiaty Adelina Hutabarat; Henry Kristian Siburian (LEGAL BRIEF, 2022)
Corruption is a contagious disease that is very dangerous and is a serious problem in every government in the world, and is not only a regional problem, but has become an international problem. Corruption spreads to educational institutions, including universities. The purpose of this study is that anti-corruption values ??in the Citizenship course for students at Budi Darma University will determine the success of students in the future as the next generation of the nation. So that it can foster the spirit to work honestly, responsibly and fairly. This study uses a qualitative approach with data collection techniques using questionnaires to provide students with an understanding of anti-corruption values ??in the Citizenship course